2009
DOI: 10.4161/cbt.8.7.7923
|View full text |Cite
|
Sign up to set email alerts
|

The Axl receptor tyrosine kinase confers an adverse prognostic influence in pancreatic cancer and represents a new therapeutic target

Abstract: Background Pancreatic cancer is a near uniformly lethal disease and a better understanding of the molecular basis of this malignancy may lead to improved therapeutics. The Axl receptor tyrosine kinase is implicated in cellular transformation and tumor progression, although its role in pancreatic cancer has not been previously documented. Results Axl labeling was present in 54 of 99 (55%), and was absent in 45 of 99 (45%) cases, respectively. Axl expression in pancreatic cancer was significantly associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
206
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(215 citation statements)
references
References 70 publications
8
206
0
Order By: Relevance
“…Axl, often coexpressed with Gas6, is detected in many metastatic cancers, indicating that autocrine Axl signaling might be a frequent consequence of EMT in many tumor types (12,24). Interestingly, Axl expression is required to maintain Snail, Slug, and Twist expression in pancreatic adenocarcinoma cells (25). This, together with our findings that these EMT transcription factors potently induce Axl expression, suggests that Axl could participate in a positive feedback loop that sustains the malignant mesenchymal phenotype of tumor cells.…”
Section: Discussionsupporting
confidence: 51%
“…Axl, often coexpressed with Gas6, is detected in many metastatic cancers, indicating that autocrine Axl signaling might be a frequent consequence of EMT in many tumor types (12,24). Interestingly, Axl expression is required to maintain Snail, Slug, and Twist expression in pancreatic adenocarcinoma cells (25). This, together with our findings that these EMT transcription factors potently induce Axl expression, suggests that Axl could participate in a positive feedback loop that sustains the malignant mesenchymal phenotype of tumor cells.…”
Section: Discussionsupporting
confidence: 51%
“…Gas6-activated Axl signaling marshalls important downstream regulators of cell motility such as Rac and Akt (Allen et al, 2002;Hasanbasic et al, 2004) and regulates haptotaxis toward vitronectin in endothelial cells (Holland et al, 2005). Recent studies support a role for Axl as a regulator of glioma, breast, lung and pancreatic tumor cell migration (Shieh et al, 2005;Vajkoczy et al, 2006;Koorstra et al, 2009) and very recently Axl was identified as an important regulator of breast cancer metastasis and survival of patients (Vajkoczy et al, 2006;Gjerdrum et al, 2010). We found that vimentin regulates Axl expression in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 87%
“…Dysregulation of Axl or its ligand Gas6 is implicated in the pathogenesis of a variety of human cancers. Overexpression of Axl has been reported in a wide array of human cancers (Craven et al, 1995;Ito et al, 1999;Berclaz et al, 2001;Sun et al, 2004;Shieh et al, 2005) and is associated with invasiveness and metastasis in lung (Shieh et al, 2005), prostate (Sainaghi et al, 2005), breast (Meric et al, 2002;Zhang et al, 2008), gastric (Wu et al, 2002) and pancreatic (Koorstra et al, 2009) cancers, renal cell carcinoma (Chung et al, 2003) as well as glioblastoma (Hutterer et al, 2008). Recently, by profiling of phosphotyrosine signaling, activated Axl protein was detected in about 5% primary tumors of non-small-cell lung cancer (NSCLC) (Rikova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%